A fourth supplement to Hand-List of Anglo-Saxon Non-Runic Inscriptions. (December 2018) - Okasha, Elisabeth
Abstract: This fourth supplement brings up to date my Hand-List of Anglo-Saxon Non-Runic Inscriptions (Cambridge, 1971), and the three supplements which appeared in Anglo-Saxon England 11 (1983), 21 (1992) and 33 (2004). This fourth supplement contains twenty-two entries and includes all the Anglo-Saxon non-runic inscriptions that have come to my notice between 2004 and 2017. Wherever possible I have personally examined all the existing inscriptions contained in this supplement. For ease of reference, this supplement follows the same pattern as before: the Entries appear first, with the same layout as before, followed by the Bibliography and Addenda.